1979
DOI: 10.1148/131.1.153
|View full text |Cite
|
Sign up to set email alerts
|

Tethered Spinal Cord Following Meningomyelocele Repair

Abstract: Of 16 consecutive patients with tethered spinal cord studied, most had undergone repair of a meningomyelocele. All were evaluated using somatosensory evoked potentials at 6 to 12-month intervals. Other possibilities include tethered filum terminale, lipomeningocele, membrana reuniens, and miscellaneous conditions (diastematomyelia, neurenteric cysts, etc.). Metrizamide myelography with polytomography was superior to gas myelography in showing a low-lying cord, obtuse nerve root angles, and a thin subarachnoid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

1981
1981
2009
2009

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(22 citation statements)
references
References 9 publications
1
21
0
Order By: Relevance
“…Somatosensory evoked potentials and elec tromyography can detect functional changes, but their value in predicting deterioration has not been shown [17,18]. Moreover, patient and parent compliance is poor because of discomfort associated with the testing proce dure.…”
Section: Discussionmentioning
confidence: 99%
“…Somatosensory evoked potentials and elec tromyography can detect functional changes, but their value in predicting deterioration has not been shown [17,18]. Moreover, patient and parent compliance is poor because of discomfort associated with the testing proce dure.…”
Section: Discussionmentioning
confidence: 99%
“…Improved post-operative outcomes have been reported when this condition was repaired promptly after the appearance of symptoms [2, 5, 11, 15, 16]. Prophylactic surgery appears to have a superior outcome to operations that are performed after the appearance of neurological deficits [10, 15, 17], because not all patients regain function once symptoms appear. This may be due to a surgical trauma or post-operative complications.…”
Section: Discussionmentioning
confidence: 99%
“…The size of the acoustic window, body habitus, scarring, and patient's age are, however, limitations that considerably restrict its accuracy and practical application [33][34][35]. Somatosenso ry evoked potentials and electromyography have been advocated as sensitive indicators of neurophysiological status in patients with tethered spinal cord [36] and also as tools in the follow-up of patients having undergone untethcring [6], The exact predictive value of this method in asymptomatic patients with signs of tethering on MRI has been questioned. Patient discomfort associated with this testing procedure has also been discussed [30,37], Cervical cord motion studies with phase-contrast MRI were reported to have an excellent predictive value in the management of tethered spinal cord [29,30,37].…”
Section: Discussionmentioning
confidence: 99%